Leadership and strategic alignment in construction - Acacio, Alexis A.
Construction management and engineering is generally thought of as a purely technical part of construction management consisting of bar charts, scheduling, estimates and bidding. While these tools may guide a company to construct a project, the management skills and techniques employed are generally not enough to ensure the success and optimization of a construction project. A successful construction project manager needs these skills. 2) General management skills, and 3) Construction engineering and technical management skills. While civil engineers are expected to be competent in construction management skills, areas of expertise in project leadership, organizational alignment and general management are lacking. Organizational alignment is the congruence and compatibility of the various activities in a construction project and determines the outcome of success or failure. This looks at the external environment in which the firm operates and the internal capabilities that it can offer. It is important that the needs of the various stakeholders in a project are satisfactorily met to ensure project success. This paper aims to describe the leadership and general management skills that are necessary for the successful completion of projects. The strategic fit that is necessary to ensure project success is described through a strategic alignment methodology. This simple process can be used by construction engineers to ensure that their project takes into account both the external environment and the congruence of internal processes within the organization.
Keywords: Strategy; Strategic alignment; Strategic construction management